2014
DOI: 10.1177/0888406414530413
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Technology to Enhance Field Experiences for Pre-Service Special Education Teachers

Abstract: Teacher educators of pre-service teachers of students with special needs face challenges in providing the unique knowledge and skills required of highly qualified special education teachers. The emerging use of various forms of virtual technology, however, offers realistic solutions to these problems. This systematic review of literature examines 14 studies that utilized these virtual technologies to increase learning outcomes for pre-service special education teachers during field experiences or courses that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 20 publications
1
34
0
9
Order By: Relevance
“…One alternative to this challenge is virtual supervision: using distance education methods (synchronous or asynchronous) to supervise student teachers as a supplemental approach to face-to-face supervision (Branburg 2001;Brintnall 2002;Hager et al 2012). Synchronous virtual supervision of preservice teachers is not a new concept in teacher education, dating back at least to the EDNET efforts in UT (Thurston and Sebastian 1996) and GA (Gruenhagen et al 1999), and continuing through several efforts focused on counseling education (Chapman et al 2011;Coursol 2004) and special education (Billingsley and Scheuermann 2014;Dymond et al 2008;Falconer and Lignugaris-Kraft 2002;Seabrooks et al 2000). However, synchronous virtual supervision has not been adopted by teacher education programs widely; projects focusing on preservice teachers have tended to emphasize asynchronous technology, such as email (e.g., Brintnall 2002;Roddy 1999), online discussion boards (Babinski et al 2001;Edens 2000), and compressed video (Branburg 2001;Fry and Bryant 2006) that do not allow direct distance supervision.…”
Section: Supervision and Virtual Supervision In Teacher Educationmentioning
confidence: 99%
“…One alternative to this challenge is virtual supervision: using distance education methods (synchronous or asynchronous) to supervise student teachers as a supplemental approach to face-to-face supervision (Branburg 2001;Brintnall 2002;Hager et al 2012). Synchronous virtual supervision of preservice teachers is not a new concept in teacher education, dating back at least to the EDNET efforts in UT (Thurston and Sebastian 1996) and GA (Gruenhagen et al 1999), and continuing through several efforts focused on counseling education (Chapman et al 2011;Coursol 2004) and special education (Billingsley and Scheuermann 2014;Dymond et al 2008;Falconer and Lignugaris-Kraft 2002;Seabrooks et al 2000). However, synchronous virtual supervision has not been adopted by teacher education programs widely; projects focusing on preservice teachers have tended to emphasize asynchronous technology, such as email (e.g., Brintnall 2002;Roddy 1999), online discussion boards (Babinski et al 2001;Edens 2000), and compressed video (Branburg 2001;Fry and Bryant 2006) that do not allow direct distance supervision.…”
Section: Supervision and Virtual Supervision In Teacher Educationmentioning
confidence: 99%
“…Furthermore, according to the researchers VWs are permanent environments where participants can interact with others, having a sense of being with them (Chau et al, 2013). Regardless of the benefits of using VWs with educational purposes, there is a dearth of studies that show the benefits of using these kinds of environments in pre-service teachers programs (Billingsley & Scheuermann, 2014). In a review of the literature, only 21 theoretical and empirical articles have been found on the use of VWs for teacher education .…”
Section: Second Life For Learningmentioning
confidence: 99%
“…As indicated by Billingsley and Scheuermann (2014) there is insufficient research that explores the benefits of using virtual environments in pre-service teachers' programs.…”
Section: Contribution Of the Present Studymentioning
confidence: 99%
See 2 more Smart Citations